2018
DOI: 10.1242/dmm.037127
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and connectivity in the developing vertebrate nervous system

Abstract: The developing nervous system depends upon precise regulation of oxygen levels. Hypoxia, the condition of low oxygen concentration, can interrupt developmental sequences and cause a range of molecular, cellular and neuronal changes and injuries. The roles and effects of hypoxia on the central nervous system (CNS) are poorly characterized, even though hypoxia is simultaneously a normal component of development, a potentially abnormal environmental stressor in some settings, and a clinically important complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 127 publications
(157 reference statements)
1
16
0
Order By: Relevance
“…During embryogenesis, the developing nervous system requires precise regulation of oxygen levels. Low levels of oxygen induce Hif gene expression, which enhances the expression of epo to regulate erythrogenesis [ 61 ]. Our results indicated that the expression levels of hif1a and hif2a were reduced in B[a] P- treated embryos.…”
Section: Discussionmentioning
confidence: 99%
“…During embryogenesis, the developing nervous system requires precise regulation of oxygen levels. Low levels of oxygen induce Hif gene expression, which enhances the expression of epo to regulate erythrogenesis [ 61 ]. Our results indicated that the expression levels of hif1a and hif2a were reduced in B[a] P- treated embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the brain is prone to hypoxia or insufficient oxygen supply due to anemia. Hypoxia may interrupt the development of the brain's nervous system and cause a series of changes and damage to molecules and neurons [35].…”
Section: Association Of Anemia With Neurobehavioral Development Of Children Aged 6-24 Monthsmentioning
confidence: 99%
“…Exposure to Hx during preterm brain development is a significant risk factor for persistent neurodevelopmental disabilities (Poets et al, 2015;Bonkowsky and Son, 2018). Preterm neonates may sustain up to 600 transient hypoxic events per week (Di Fiore et al, 2010).…”
Section: Discussionmentioning
confidence: 99%